Los instrumentos musicales y su incidencia en el desarrollo auditivo en el aula taller de la carrera de educación parvularia de la Universidad Tecnica de Cotopaxi en la parroquia Eloy Alfaro del cantón Latacunga de la provincia de Cotopaxi en el periodo 2012 - 2013 - Coro Cisneros, Norma Rocío (2013)
Teaching children music was like a game. However, it was a major stimulus to develop their skills and sharpen their skills and sensitivity. That is, playing a musical instrument has many benefits to small, so instruments were classified by the way you play and the tone generated with the purpose of generating a great music scene. This research was also based on the development of speech, language and hearing as they are an important part of the lives of human beings. In speech described the ability to make sounds, while language referred to the ability to understand and use these sounds. The hearing was necessary for the proper development of both speech and language. In the language mentioned is a basic tool for interpersonal relationships, and was an act of communication to exchange ideas and emotions. Was found closely linked to intelligence and thought because to get to the language we must be able to imagine and remember, have the symbol of things without them being ahead. It took into account musical education and that through music we express feelings, but this was achieved with the application of a methodology and as a result gives us a magnificent body and musical expression.